Investigating Vocabulary Acquisition And Vocabulary Learning Strategies Through Short Narrative Texts Among Thai Efl Tertiary Students - Jarinya, Srimanee (2021)
This study investigated vocabulary acquisition (VA) and vocabulary learning strategies (VLS) use of Thai EFL graduates of a government university in southern Thailand through English narrative readings that inserted fifteen target words into each reading text. The main purpose of the reading treatment was reading comprehension skills. The study also examined implications for EFL vocabulary learning and teaching in Thai context. The sample of forty Thai EFL graduates was selected from one group of first year students majoring in Accountancy from a southern Thailand government university. Data were collected using a combination of information-elicitation techniques: (1) test of vocabulary gains (2) vocabulary learning strategy questionnaire and (3) semi-structured interview. The questionnaire survey and the interview were used to elicit information about their vocabulary learning strategy use and vocabulary learning experiences. The data analysis was both quantitative and qualitative to seek for in-depth findings. Research findings showed that firstly the participants’ English-Thai and Thai-English word knowledge measured by the word meaning tests were more satisfactory in comparison to their word comprehension in context tests. Secondly, the participants seem not good at using various words or phrases to express meaning in other contexts apart from the provided reading tasks.